A Study On The Compatibility Of Look Ahead: An English Course 2 For Senior High School Students Year XI Textbook With School Level-Based Curriculum - Purwaningrum, Endah Aprilia (2013)
The major purpose of this study is to know whether the materials in "Look Ahead: An English Course 2 For Senior High School Students Year XI" written by Th. M. Sudarwati, Eudia Grace, and published by PENERBIT ERLANGGA in 2007 textbook compatible or not with School Level-based Curriculum and how far its compatibility is. Then to know whether the textbook provide communicative exercises or not based on 4 criteria (information gap principle, jigsaw principle, information transfer principle, and problem solving principle) and how its communicativeness. The subject of the study is the material in the textbook itself. In analyzing the textbook, the writer uses descriptive method. In analyzing data, the writer does five steps. Those are: classifying the kinds of the materials of four language skills in the textbook based on the school level-based curriculum and also the kinds of its communicative exercises based on four criteria chosen, making comparison of how the materials and exercises of the textbook developed the four language skills suggested by the School Level based Curriculum and also the criteria of communicative exercises based on four criteria chosen, matching the score based on the measurement which has been mentioned, counting the percentage to the total of the language skills and communicative exercises developed in the textbook, and drawing conclusion and suggestion based on the data analysis. The results show that there are thirty five (35) listening indicators which are developed in the textbook out of forty seven (47) indicators, then the total number of speaking indicators is twenty nine (29) indicators out of thirty five (35) indicators, while the total number for reading indicators is eleven indicators (11) out fifteen (15) indicators, and the total number for writing skill is nine (9) indicators out of fourteen (14) indicators. So, the total number of indicators of all language skills is eighty four (84) indicators out of one hundred and eleven (111) indicators. So, this book is compatible with the indicators in School Level-based Curriculum. The other finding shows that the compatibility of the materials in the textbook with the indicators in School Level-based Curriculum is 75, 67%. It means that the textbook is good in supporting and developing skills suggested by School Level-based Curriculum. Then, there are four kinds of communicate exercise are available in the textbook: information gap principle, jigsaw principle, information transfer principle, and problem solving principle. So, the result of this study shows that the percentage for this aspect is 100%. It means that the quality of the communicative exercises developed in the textbook is very good.